LIMITATIONS BETWEEN COMMERCIAL CONTRACTS AND CONSUMER CONTRACTS - Tridarani, Marsella; Ahmady, Yarni Nikita (Tadulako Law Review, 2020)
Commercial Contracts and Consumer Contracts have a fundamental difference however in practice people still can not distinguish between the two. These differences include the principles, scope, the parties who are involved and the settlement of its dispute. Moreover, the terms of the contract can not be separated from BW, although the consumer contract is specifically regulated in Law No. 8 of 1999 on Consumer Protection. These contractual arrangements are also governed by the Convention on International Sales of Goods (CISG), Unidroit Principles of International Commercial Contracts (UPICC), the settlement of disputes between the two contracts are different in which the non litigation process ofÂ  consumer contracts dispute can be settled through BPSK.